Explorative life-cycle assessment of renovating existing urban housing-stocks. (November 2019) - Österbring, Magnus; Mata, Érika; Thuvander, Liane; Wallbaum, Holger
Abstract: Urban building-stocks are responsible for a significant share of resource and energy use. To quantify the potential for reducing energy and environmental impact, building-stock modelling (BSM) is commonly used. Recently, the focus of BSM has expanded to include environmental impacts and life-cycle assessment (LCA). However, impact categories are often limited to climate change and representative buildings are often used. In addition, the future state of the stock is often calculated as a step-change to highlight the technical potential of an ideal future state. The aim of this paper is to assess the environmental impact of the future development of an urban housing-stock under business-as-usual scenarios using a building-specific GIS based model applied to the multi-family building stock of the City of Gothenburg. This paper uses an explorative LCA to account for environmental impacts based on dynamic uptake of common renovation measures and resulting energy savings until 2050. Two main scenarios are used where the renovation logic is based on either end-of-life of components or cost-effectiveness and further divided using limiting factors regarding investment capacity and annual share of the stock to be renovated. Results show possible energy savings of up to 23% and a corresponding 31% reduction in greenhouse-gas emissions. Greenhouse-gas emissions avoided due to reduced energy demand are offset by up to 65% by accounting for material use due to construction related renovation measures. For scenarios that favour construction related interventions, PV panels are responsible for the major part of the environmental impact across the 15 mid-point indicators used. Highlights: Environmental impact of renovation is assessed for an urban housing-stock. Environmental impact is assessed using 15 impact categories. Common renovation measures and scenarios following current trends is used. Reductions in greenhouse-gas emissions of up to 31% due to reduce energy use. Up to 65% of greenhouse-gas emissions are offset due to material use.